2014
DOI: 10.1002/prep.201300114
|View full text |Cite
|
Sign up to set email alerts
|

Explosive Initiation of Various Forms of Ti/2B Reactive Materials

Abstract: The reactivity of titanium and boron mixtures under detonation initiation in air is examined experimentally in a constant volume blast chamber. Fine powder mixtures and mechanical alloys are pressed into compacts and are ignited using an HMX‐based explosive initiated with both single point and triple point detonator configurations. Transient pressure measurements, optical imaging, pyrometry, and spectroscopy are performed to analyse the reaction. All mixtures show no significant enhancement in the primary blas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 8 publications
0
15
0
Order By: Relevance
“…Regarding fragmentation mechanisms, the porosity of a reactive material mixture does promote fine fragmentation. A large porosity, however, results in a deficit in TMD, thus leading to a low mechanical strength [5], which conflicts with the definition of a SRM solid. From the intrinsic grainscale properties of dissimilarity and reactivity, fine fragmentation mechanisms have been proposed, using structural discontinuity and impedance mismatch within a SRM solid of multiple dissimilar materials [6][7][8][9], and a reactive hot spot concept.…”
Section: Introductionmentioning
confidence: 93%
“…Regarding fragmentation mechanisms, the porosity of a reactive material mixture does promote fine fragmentation. A large porosity, however, results in a deficit in TMD, thus leading to a low mechanical strength [5], which conflicts with the definition of a SRM solid. From the intrinsic grainscale properties of dissimilarity and reactivity, fine fragmentation mechanisms have been proposed, using structural discontinuity and impedance mismatch within a SRM solid of multiple dissimilar materials [6][7][8][9], and a reactive hot spot concept.…”
Section: Introductionmentioning
confidence: 93%
“…A different set of experiments with shock‐initiated RSMs addresses applications, in which an RSM is dispersed and initiated by interaction with a shock wave produced by a high explosive (HE) . In one of the experiments, a pressed pellet of mechanically alloyed B–Ti powder was placed directly on top of an HE pellet.…”
Section: Characterization Of Rsmsmentioning
confidence: 99%
“…Although low density and strength of Al‐PTFE composites severely limits their applications, such materials were studied rather extensively, representing a common reference system for many RSMs developed recently. In addition to metal‐fluoropolymers, the types of RSMs described in the literature include thermites, for example, reactive intermetallic systems, such as Al–Ni, for example, metal‐metalloid systems, including B–Ti, B–Zr, for example, systems forming metal carbides, for example, and simply composites and alloys combining materials with different desired properties, for example, tungsten with a high density with zirconium or hafnium, metals with a relatively high reactivity . Along with the composition, design of composite RSMs and the methods used for their testing vary widely, depending on the intended application, properties of individual components, and capabilities available to the material designers.…”
Section: Introductionmentioning
confidence: 99%
“…Reactive liners have been used in various energeticd evices [1][2][3],m ostly relying on exothermic reaction between components of the liner material. While aluminum is the most widely used metal fuel additive to propellants, explosives, and pyrotechnics [4,5],u se of aluminum powdersc ombined with other components in reactive materials was explored only recently [6][7][8][9][10].M ost of the recentw ork focused on laboratory studies characterizing low-rate reactions in such materials;t hermo-analyticale xperiments are used widely,i np articular.V ery few studies can be found, where blast or shock initiation of new reactivem aterials is characterizede xperimentally with time-resolved measurements [11,12].T ime-resolved measurements are important in understanding the reaction mechanisms and further optimizationo fr eactive materials based on new components, alloys, and composites, whichb ecome availablea saresult of recent research.…”
Section: Introductionmentioning
confidence: 99%
“…
1IntroductionReactive liners have been used in various energeticd evices [1][2][3],m ostly relying on exothermic reaction between components of the liner material. While aluminum is the most widely used metal fuel additive to propellants, explosives, and pyrotechnics [4,5],u se of aluminum powdersc ombined with other components in reactive materials was explored only recently [6][7][8][9][10].M ost of the recentw ork focused on laboratory studies characterizing low-rate reactions in such materials;t hermo-analyticale xperiments are used widely,i np articular.V ery few studies can be found, where blast or shock initiation of new reactivem aterials is characterizede xperimentally with time-resolved measurements [11,12].T ime-resolved measurements are important in understanding the reaction mechanisms and further optimizationo fr eactive materials based on new components, alloys, and composites, whichb ecome availablea saresult of recent research.In this paper,s hock initiation is characterized experimentally for aluminum and for differently prepared Al·Mg alloyed powders.A luminum-magnesium alloys have long been used in various pyrotechnic compositions [13][14][15]; they have also been considered for ab roader rangeo fe nergetic formulations [16,17].R ecently,m echanically alloyed Al·Mg powders were prepared with controlledp article sizes and improved combustionc haracteristics [18,19].W hile the total theoreticalv olumetric or gravimetric combustion enthalpy is reduced when part of aluminum is replacedw ith magnesium,t he efficiency of reaction and its completeness may improve. Significance of such effectsf or reactive liners prepared using metal or alloy powders is addressed in the presente xperiments.
2E xperimental Section
MaterialsSpherical H-2 aluminum powder by ValimetI nc.
…”
mentioning
confidence: 99%